Securitization Impact on Bank Risk: Empirical Evidence from the U.S. Bank Holding Companies - Liu, Liping (2019)
This paper examines the relation between securitization and bank risk of U.S. bank holding companies during 2011 - 2018. Using different measures of bank risk, the finding shows that the securitization reduces bank risk. It also shows that Loan, Equity, GDP growth rate have positively and significantly influence on the bank risk while Net interest margin may play a role in reducing the banks risk in a statistically significant manner. Using different proxies for the bank risk, it is observed that the banks still achieve the credit risk transfer function and realize a reduction of risk exposure when they actively involved in the securitizations. Furthermore, these findings are relatively valid and robust to different variables used to measure the securitization activities, as well as to different estimation approaches. The findings suggest that, in its aftermath of the financial crisis, banks may enhance their performance in risk control and capital management, investors become more rational and careful in investment decision making process, and financial system is upgraded with new brochure.